When Should Irrigators Invest in More Water‐Efficient Technologies as an Adaptation to Climate Change?. Issue 11 (16th November 2018) - Malek, Keyvan; Adam, Jennifer; Stockle, Claudio; Brady, Michael; Rajagopalan, Kirti
Abstract: The western U.S. is expected to experience more frequent and severe droughts as a result of climate change, with potentially large impacts on agricultural production and the economy. Irrigated farmers have multiple options for minimizing the impact of drought including switching to more efficient irrigation technologies. More efficient technologies that increase the fraction of the water available to the crop root zone would allow farmers to maintain current production levels with less water. However, these systems are capital intensive. The objective of this study is to explore when (and under what climatic conditions) it makes economic sense for farmers to invest in new irrigation systems. We examine this in the Yakima River Basin in Washington State of the U.S. We use VIC‐CropSyst, a large‐scale grid‐based modeling framework that mechanistically simulates hydrologic and agricultural processes. Water supply simulated by VIC‐CropSyst drives a river system and water management model (YAK‐RW). A computational platform was developed to perform the economic analysis for each grid cell, crop type, and future climate scenario separately, which allowed us to explore whether the implementation of more efficient irrigation systems would be economically viable. Our results indicate that investing in a more efficient irrigation system improves agricultural economy of the Yakima River Basin (9% −25%). We also show that at the farm level, more significant droughts can provide economic incentives for investment up to a point . For severe climate change projections, droughts become frequent and severe enough that economic benefits of improving water use efficiency do not exceed investment costs. Key Points: Climate change increases the frequency and severity of drought; however, in some cases, this does not provide enough economic incentive for investment in a new irrigation system At the farm level, the viability of investment depends on crop type and severity of droughts Net economic benefit at the basin scale depends on the cropping mix